Aggregation enhanced two-photon fluorescence of organic nanoparticles. (April 2015) - Shi, Xingrui; Xu, Zhenzhen; Liao, Qing; Wu, Yishi; Gu, Zhanjun; Zheng, Renhui; Fu, Hongbing
Abstract: Two-photon excited ﬂuorescence bio-probes have obtained a great deal of interests in biological imaging and sensing applications. We synthesized a new donor–π–acceptor molecular (BNSN) with strong intramolecular charge-transfer (ICT). Interestingly, different from conventional ICT compounds, BNSN molecules present an unusual ICT phenomenon, leading to a red-shifted emission and an increased fluorescence quantum yield ( Φ ) with increasing the polarity of solvents. Moreover, the fluorescence intensity and two-photon absorption cross-section all enhanced when the molecules aggregated. The nanoparticles of BNSN exhibit strong two-photon excited ﬂuorescence in aqueous media, exhibiting the property of aggregation-enhanced two-photon fluorescence (AE-TPF). Our results demonstrate that the BNSN molecules with AE-TPF effect provide a new molecular type to construct efﬁcient two-photon excited ﬂuorescence nano-probes for bio-imaging. Graphical abstract: Highlights: We synthesized and investigated the photophysical properties of a new donor–π–acceptor molecule BNSN. BNSN exhibits a red-shifted emission and an unconventional dramatic increase of emission efficiency in polar solvent. The fluorescence intensity and two-photon absorption cross-section all enhanced when the molecules aggregated. The nanoparticles of BNSN exhibited aggregation-enhanced two-photon fluorescence in aqueous media. Cell imaging capability in living cancer cells was examined with low toxicity and high photostability.